ANTIDIABETIC EFFECTS OF INDONESIAN BAY LEAVES (SYZYGIUM POLYANTHUM) EXTRACTS THROUGH DECREASING ADVANCED GLYCATION END PRODUCTS AND BLOOD GLUCOSE LEVEL ON ALLOXAN-INDUCED HYPERGLYCEMIC WISTAR RATS - Wahjuni, Sri; Mayun Laksmiwati, Aaia; Manuaba, Ida Bagus Putra (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Increased production of reactive oxygen species is one of the causes of hyperglycemia. This study aims to determine the effectiveness of Indonesian bay leaves (Syzygium polyanthum) extracts as an antidiabetic agent in decreasing blood glucose and advanced glycation end products (AGEs) level of alloxan-induced hyperglycemic Wistar rats. Methods: This research is a real experimental study with pre- and post-test control group design. The study begins with the induction of hyperglycemia in 40 Wistar rats using alloxan. Subsequently, hyperglycemic rats were divided into 6 groups, namely, the positive control group (P0); the treatment group by not giving the intake of Indonesian bay leaf (P1); the treatment group was given the extract of Indonesian bay leaves (S. polyanthum) 0.5 mg/kg body weight/day (P2); treatment group given Indonesian bay leaves extract 2.0 mg/kg body weight/day (P3); treatment group given Indonesian bay leaves 5.0 mg/kg body weight/day (P4), and P5 was treatment group with glibenclamide (hyperglycemia-lowering medication). Results: In the treatment of P1, P2, P3, P4, and P5 groups, it can be seen that there are decreases of blood glucose and AGEs level between pre- and post-test comparison. However, the most significant drop in mean plasma glucose level was observed at the dosage 5.0 mg kg-1 (P4). Conclusion: The administration of Indonesian bay leaf extracts at a dose of 5.0 mg/kg body weight/day have an antidiabetic effect through decreasing blood glucose and AGEs level in alloxan-induced hyperglycemic Wistar rats.